HDAC11 Regulates Glycolysis through the LKB1/AMPK Signaling Pathway to Maintain Hepatocellular Carcinoma Stemness - Bi, Lei; Ren, Yidan; Feng, Maoxiao; Meng, Peng; Wang, Qin; Chen, Weiping; Jiao, Qinlian; Wang, Yuli; Du, Lutao; Zhou, Fuqiong; Jiang, Yucui; Chen, Feiyan; et al. (Cancer research (Chicago, Ill.), 2021)
Hepatocellular carcinoma (HCC) contains a subset of cancer stem cells (CSC) that cause tumor recurrence, metastasis, and chemical resistance. Histone deacetylase 11 (HDAC11) mediates diverse immune functions and metabolism, yet little is known about its role in HCC CSCs. In this study, we report that HDAC11 is highly expressed in HCC and is closely related to disease prognosis. Depletion of HDAC11 in a conditional knockout mouse model reduced hepatocellular tumorigenesis and prolonged survival. Loss of HDAC11 increased transcription of LKB1 by promoting histone acetylation in its promoter region, thereby activating the AMPK signaling pathway and inhibiting the glycolysis pathway, which in turn leads to the suppression of cancer stemness and HCC progression. Furthermore, HDAC11 overexpression reduced HCC sensitivity to sorafenib. Collectively, these data propose HDAC11 as a new target for combination therapy in patients with kinase-resistant HCC. SIGNIFICANCE: This study finds that HDAC11 suppresses LKB1 expression in HCC to promote cancer stemness, progression, and sorafenib resistance, suggesting the potential of targeting HDAC11 to treat HCC and overcome kinase inhibitor resistance.